Pemetaan Sosial Pola Pemberian MPASI Dini dalam Konteks Risiko Stunting di Bangkalan - Madura - Hoiriyeh Hoiriyeh; Hetti Mulyaningsih; Aminah Dewi Rahmawati (Education : Jurnal Sosial Humaniora dan Pendidikan, 2026)
The issue of stunting is one of  the problems that threatens the quality of human sesources (HR) in Indonesia. One contributing factor is the early introduction of complementary feeding providing complementary foods before the age of six months. Social influence from close family members and community  figures also plays a significant role in shaping parental behaviors, leading to the continued prevalence of early complementary feeding practices in Indonesia particularly in Bangkalan Regency. This study aims to map the social behaviors associated with early complementary feeding in Bangkalan Regency. A qualitative research methodology was employed, incorporating in-depth interviews, field observations, and supporting documentation that supportsthe research being conducted by the researcher. The results of the study show that many people in Bangkalan Regency still practice early complementary feeding for toddlers under 6 months of age. This is due to parents’ lack of understanding about fulfilling their children’s nutritional needs, as well as being influenced by the socio-cultural constructs in community life and the role of the family in decision-making regarding infant feeding, which increases the risk of stunting in children. The results of this research are expected to serve as a reference for stakeholder, particularly the government and health workers, in developing nutritional intervention programs.